Reviews. - Cherkaoui, Driss; Stewart, Devin; Hoffiz III, Benjamin T.; Heath, Peter; McLarney, Ellen; Stone, Christopher; Antoon, Sinan; Cross, Carmen; Rodgers, Jonathan (Journal of Arabic Literature, 2003)
Reviews several books on Arabic literature. "Literary Structures of Religious Meaning in the Qur'ãn," edited by Issa J. Boullata; "Arabic Grammar: A Reference Guide," by John Mace; "The House on Arnus Square," by Samar Attar; "Images of Enchantment: Visual and Performing Arts of the Middle East," edited by Sherifa Zuhur.